Pneumatic Reciprocating Hack Saw Machine - Manavalan, S. (International Journal of Psychosocial Rehabilitation, 2019)
The hacksaw is a metal cutting machine tool designed to cut metal by applying pneumatic pressure. The machine is exclusively intended for mass production, and they represent a faster and more efficient way to cut metal. Hacksaws are used to cut thin and soft metals. The operation of the unit is simplified to a few simple operations involving a cylinder block and piston arrangement. There are numerous types of cutting machines in the engineering field that are used to fulfill the requirements. We are interested in introducing pneumatic systems in hacksaw machines. The main function of a pneumatic hacksaw is to cut thin and soft metals with pneumatic power.